Association of Neutrophil/Lymphocyte Ratio and Retinal Vein Occlusion. Issue 4 (July 2015) - Dursun, Ayhan; Ozturk, Sultan; Yucel, Hasan; Ozec, Ayse Vural; Dursun, Feyza Gulac; Toker, Mustafa Ilker; Erdoğan, Haydar; Arici, Mustafa Kemal; Topalkara, Aysen
Purpose: To evaluate the association between neutrophil/lymphocyte ratio (NLR) and the development of retinal vein occlusion (RVO). Methods: Forty patients were included in the study. Forty age- and sex-matched healthy volunteers were recruited as the control group. The RVO diagnosis was made clinically, based on the findings of fundus examination. The NLR and file records of the patients and the control group were compared. Results: The mean age of patients was 64 ± 12 years. Neutrophil levels were higher in RVO patients compared to the control subjects (5.1 ± 1.9 vs 3.6 ± 1.0, p<0.001). Lymphocyte levels were lower in RVO patients compared with the control subjects (2.0 ± 0.7 vs 2.6 ± 0.9, p = 0.005). The NLR was significantly higher in RVO patients compared with the control subjects (3.0 ± 2.7 vs 1.5 ± 0.3, p<0.001). According to the receiver operator characteristics curve analysis, the optimal cutoff value of NLR to predict RVO was >1.89, with 72.5% sensitivity and 100% specificity. Conclusions: The current study demonstrated that higher NLR was associated with the development of RVO. The NLR may be used as a predictive tool for identifying risk for RVO.